(untitled) (Indian Journal of Animal Production and Management, 2025)
Background: Neonatal diarrhea represents a major cause of morbidity and mortality in pre-weaning lambs and kids. Prebiotic supplementation may improve gut health by modulating microbiome composition and enhancing mucosal immunity. Objective: This study aimed to evaluate the effects of mannan-oligosaccharides (MOS), fructo-oligosaccharides (FOS), and their combination on gut microbiome, mucosal immunity, systemic cytokines, and growth performance, and develop a Gut Health Index (GHI) for health status prediction. Methods: One hundred sixty pre-weaning animals (80 local crossbred lambs + 80 kids; 7±2 days old) were allocated to four groups: Control, MOS (4 g/day), FOS (4 g/day), and MOS+FOS (2+2 g/day) for 8 weeks. Fecal samples were analyzed by 16S rRNA gene sequencing (V3–V4 region, Illumina MiSeq). Mucosal immunity markers (fecal sIgA, β-defensins, MUC2, ZO-1 mRNA) and systemic cytokines (IL-10, TNF-α, TGF-β) were measured. Growth performance and diarrhea incidence were recorded. ROC analysis was performed. Results: MOS+FOS synergistically improved microbiome composition: Lactobacillus increased 2.8-fold, Bifidobacterium 3.2-fold, while Escherichia decreased 68% and Clostridium 54%. Alpha diversity (Shannon index) increased from 3.42 to 4.86. Mucosal immunity enhanced: sIgA 2.3-fold, β-defensin-1 3.0-fold, MUC2 mRNA 2.68-fold. Systemic IL-10 increased 84% while TNF-α decreased 49%. ADG improved 18.6% and diarrhea incidence decreased from 32.5% to 7.5%. Lactobacillus/E. coli ratio showed strongest predictive performance (AUC = 0.91). The proposed GHI achieved 88.6% accuracy. Conclusion: Combined MOS+FOS supplementation synergistically improves gut microbiome, mucosal immunity, and growth performance in pre-weaning small ruminants, with the GHI providing a practical tool for health assessment.